O contexto sócio-jurídico-político da saúde e a participação democrática: controle social das políticas públicas de saúde - Klein, Arthur Henrique (Universidade do Vale do Rio dos Sinos, 2013)
The theme involving public policies and their effectiveness has been object of study and research for centuries. The forms to control and supervise the actions of public programs gain relevance in the contemporary scenery, where society claims for effective action and managements of results. The ways the policies of public programs are to be controlled and supervised gain particular relevance in the contemporary political scenery, as today´s society is more politically aware and claims for more effective action and better final results. New technologies, with their peculiar forms of contextualization and information sharing, have inaugurated a new form of social control, which acts powerfully and exerts a new function, which transcends the simplistic representative democracy of the popular vote. As good government is no longer seen only as a citizen's right but as a duty of public officials when performing their governmental functions, the power to control the acts of the government officials, undertaken by the civil society in its various fields of action, becomes a most effective way to combat the fraudulent use of public resources. Upon giving priority to public finances control and to effective public health systems, I have tried to analyze the legislation that deals with the subject, together with the principles governing the conduct of public officials. The complexity involving safeguarding the right to health, in its broadest conception, has to do with assessing the challenges the state and federal governments have to face, namely, shortage of medical professionals and budget constraints, and with examining how the judiciary is managing the problems involved in preserving this fundamental right. The active participation of every citizen in the decision-making process concerning the implementation of public health policies, as an exercise of citizenship and social control, establishes a new landmark in today’s democracy, which has already been called a pro-health democracy.
Keywords: Políticas públicas; Sistema de saúde; Controle social; Participação popular; Democracia sanitária; Public policies; Health systems; Social control; Popular participation; Pro-health democracy; ACCNPQ::Ciências Sociais Aplicadas::Direito